Efektivitas Pelaksanaan Corporate Social Responsibility Di Perusahaan Daerah Air Minum (PDAM) PT Adhya Tirta Batam - Maya Aritonang, Nadya Trisha; Suka Arjawa, I Gusti Putu Bagus; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
Corporate Social Responsibility (CSR) is one of the company's obligations that must be fulfilled as a form of commitment in carrying out business activities based on ethical values ??so as to create sustainable development and have concern for the environment and society. The approach used in this research is a qualitative approach with descriptive-explanative research type. The theory used in this research is Triple Bottom Line theory by John Elkington. The implementation of CSR activities carried out by PT Adhya tirta Batam can be said to be effective, it can be seen that not only the community benefits from the CSR activities carried out, but ATB companies also feel the benefits where ATB gets a good perception from the community so that company productivity increases more and more customers and the company is growing well. Keywords: Corporate social responsibility, Effectiveness, PT Adhya Tirta Batam, John Elkington